Next step, multiply both sides by (.01-x)


gather terms, put in standard binomial form, use the quadratic equation, and solve for x.

is the standard binomial x^2+.022x-1.2x10^-4

  1. 👍
  2. 👎
  3. 👁
  1. yes. That is the correct quadratic equation. Now solve for x. Then (H^+) = 0.01 + x and pH = -log(H^+).

    1. 👍
    2. 👎
  2. yes.

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator Multiply both sides by 2. 2A = (2*1/2)h(b1 + b2). 2*1/2 on the right side

  2. algebra

    Write the polynomial in standard form. Then name the polynomial based on its degree and number of terms. 2 – 11x^2 – 8x + 6x^2 A. –5x^2 – 8x + 2; quadratic trinomial B. –5x^2 – 8x; quadratic binomial C. –6x^2 – 8x

  3. math

    The lower leg of a right triangle is 8 cm in length. Calculate the other two knowing that the sides of the triangle form an arithmetic sequence. please give me step by step answers thanks

  4. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

  1. Algebra 2

    Read the following proof of the polynomial identity a3+b3=(a+b)3−3ab(a+b). Step 1: a3+b3=a3+3a2b+3ab2+b3−3ab(a+b) Step 2: a3+b3=a3+3a2b+3ab2+b3−3a2b−3ab2 Step 3: a3+b3=a3+3a2b−3a2b+3ab2−3ab2+b3 Step 4: a3+b3=a3+b3

  2. mathematics

    A bug spray's effectiveness decreases over time. After h weeks, it retains only half of its effectiveness, and this trend continues. A function that represents this is Q(t) = 30•6^5-1 A scientist testing the bug spray tried to

  3. Math

    Multiply the binomial and the trinomial: (x – 5)(x 2 + 5x + 25 step by step

  4. Variable

    SOLVING EQUATIONS WITH THE VARIABLE ON BOTH SIDES Solve the equation. Then check your solution. 4x-9 = 7x+12 Just remember that one can add, subtract, multiply, divide, etc but whatever is done to one side must be done to the

  1. algebra1

    How do i solve this problem? 2(x-3)-3(x+5)=3(x-2)-7 what are the steps to solving this equation? HELP!!! Multply out the parentheses and then combine terms First step: 2x - 6 -3x -15 = 3x -6 -7 -x -21 = 3x -13 Nox add x + 13 to

  2. algebra

    Which could be a first step in solving the equation 1/4x+1/2=3/4x in an efficient way? Select two answers. A.multiply by 4 on both sides B.multiply by 2x on both sides C.subtract 1/4x from both sides D.add 1/2 to both sides plz

  3. Math

    Which could be a first step in solving the equation 1/4x + 1/2 = 3/4x in an efficient way? Select two answers. A. Multiply by 4 on both sides*** B. Multiply by 2x on both sides C. Subtract 1/4x from both sides D. Add 1/2 to both

  4. Algebra

    Solve Q= (N-S)/ N for N So when I multiply both sides by N I get Q(N)= N-S I know I am doing something wrong, the answer is in the book which is N=S/(1-Q)but I don't understand were the 1 comes from. Could you write it out step by

You can view more similar questions or ask a new question.